Writing the lost generation : expatriate autobiography and American modernism - Monk, Craig, 1969- (University of Iowa Press, 2008)
In Writing the Lost Generation, Craig Monk unlocks a series of neglected texts while reinvigorating our reading of more familiar ones. Well-known autobiographies by Malcolm Cowley, Ernest Hemingway, and Gertrude Stein are joined here by works from a variety of lesser-known, but still important, expatriate American writers, including Sylvia Beach, Alfred Kreymborg, Samuel Putnam, and Harold Stearns. By bringing together the self-reflective works of the Lost Generation and probing the ways the writers portrayed themselves, Monk provides an exciting and comprehensive overview of modernist expatri.